Democracy in the Indonesian Digital Public Sphere: Social Network Analysis of Twitter Users' Responses to the Issue of Nationalism Knowledge Test at the Corruption Eradication Commission (TWK-KPK) - Suwandi Sumartias; Dwia Aries Tina Pulubuhu; Sudarmono Sudarmono; Achwan Noorlistyo Adi; Eny Ratnasari (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2023)
The mobility restriction during the COVID-19 pandemic did not stop the public from expressing their opinions. Since they could not go on demonstrations, they moved democracy to the digital sphere, such as on Twitter. Previous research has shown that Twitter users in Indonesia use the platform to express political views and opinions on governmental issues. The issue of the Nationalism Knowledge Test (TWK) at the Corruption Eradication Commission (KPK) was a trending topic on Twitter for a while. The issue spurred discussions on Twitter when 75 employees did not pass the KPK-TWK on May 2021. The discussion then stopped for a moment before picking up again during the official dismissal of the employees on 30 September 2021. This article focuses on the social network analysis of the public’s responses to this issue on Twitter. Social network data were collected using Drone Emprit from May to October 2021 and analyzed using Gephi to generate graphical representations of the social networks. The results reveal the structure of the movement was centralized and dynamic. Regarding the dissemination of information, the most central was news media and anti-corruption activists’ accounts. These accounts mobilized the community on Twitter to make a critical social movement. This means that the digital sphere can be an evolution of democracy form and activism, especially in the anti-corruption movement.